Limitations in the description of conformational preferences of C-disaccharides: The (1 → 3)-C-mannobiose case - Raich, Ivan; Lövyová, Zuzana; Trnka, Ladislav; Parkan, Kamil; Kessler, Jiří; Pohl, Radek; Kaminský, Jakub (Carbohydrate research, 2017)
Conformational preferences of two C-glycosyl analogues of Manp-(1 → 3)-Manp, were studied using a combined method of theoretical and experimental chemistry. Molecular dynamics was utilized to provide conformational behavior along C-glycosidic bonds of methyl 3-deoxy-3-C-[(α-d-mannopyranosyl)methyl]-α-d- and l-mannopyranosides. The OPLS2005 and Glycam06 force fields were used. Simulations were performed with explicit water (TIP3P) and methanol. Results were compared with a complete conformational scan at the MM4 level with the dielectric constant corresponding to methanol. In order to verify predicted conformational preferences, vicinal 3JHH NMR coupling constants were calculated by the Karplus equation on simulated potential energy surfaces (PES). A set of new parameters for the Karplus equation was also designed. Predicted 3JHH were compared with experimental data. We also used reverse methodology, in which the 3JHH coupling constants were calculated at the DFT level for each family of (ϕ, ψ)-conformers separately and then experimental values were decomposed onto calculated 3JHH couplings in order to obtain experimentally derived populations of conformers. As an alternative method of evaluation of preferred conformers, analysis of sensitive 13C chemical shifts was introduced. We were able to thoroughly discuss several fundamental issues in predictions of preferred conformers of C-saccharides, such as the solvent effect, reliability of the force field, character of empirical Karplus equation or applicability of NMR parameters in predictions of conformational preferences in general.
Keywords: Molecular Dynamics Simulation; glykosidy; Disaccharides; Glycosides; magnetická rezonanční spektroskopie; Magnetic Resonance Spectroscopy; disacharidy; simulace molekulární dynamiky; Molecular Conformation; mannosidy; Mannosides; molekulární konformace